Two-stage constructed wetland systems for polluted surface water treatment. (1st November 2019) - Saeed, Tanveer; Majed, Nehreen; Khan, Tanbir; Mallika, Hena
Abstract: Two pilot scale wetland systems were studied for the removal of organics, nitrogen, phosphorus and coliform from polluted surface water. Each system consisted of two units: a vertical flow (VF) wetland packed with construction materials gravel, brick or organic sugarcane bagasse, followed by a surface flow (SF) or floating treatment (FT) wetland. All wetland units were planted with Phragmites . The wetland systems were operated under constant and shock hydraulic load (HL) periods. Input COD, N, P loadings ranged between 61 and 2181, 7–1040, 2–194 g/m 2 d, respectively across first stages of each system. Mean removal percentages ranged between 39 and 97, 11–83, 20–100% and 4–85, 16–86, 1.4–100% across first and second stage wetlands, respectively. Mass balance analyses revealed ≤7% N and ≤14% P accumulation in plants; as such, microbial and adsorption kinetics controlled removal dynamics. Nitrification was the limiting nitrogen removal factor in first stage wetlands; organic carbon was supplied by the employed media. Aerobic organics removal and nitrification were diminished during initial stage of shock load periods. In contrast, second stage SF and FT wetlands showed stable removal performances under similar conditions. Resuspension of settled particles decreased removal performance in second stage wetlands, as shock periods progressed toward final stage. Coliform mortality was increased in second stage wetlands. Physico-chemical properties of brick materials in construction material based VF wetland and hanging root volume inside the water column of FT wetland supplemented removal performance. In general, this study provides evidence on potential application of constructed wetlands for polluted surface water treatment. Highlights: Adsorption and microbial pathways controlled pollutant removal kinetics. Physico-chemical properties of construction materials supplemented removals. Shock loads influenced aerobic removals in VF wetland units. Hanging root counter-balanced shock load impact in FT wetland. Two-stage constructed wetlands showed stable pollutant removal performance.